Formation universitaire pour les intervenant·es en protection de la jeunesse au Québec : quand les droits et la participation des enfants passent au second plan - Vicky Lafantaisie; Rosita Vargas Diaz; Sophie T. Hébert; Isabelle-Ann Leclair Mallette; Alexandra Lachapelle-Ouellette; Geneviève Pagé; Annie Bérubé; Annie Devault; Mélissa David (Sociétés et Jeunesses en Difficulté)
Given the lack of content related to children’s rights and child participation in current university training programs, and the new shift calling for greater child and youth participation (Commission spéciale sur les droits des enfants et la protection de la jeunesse - CSDEPJ, 2021; Lafantaisie et al., 2024), training needs of child welfare workers in Quebec should gather attention. The aim of this article is to present and discuss the training priorities identified by practitioners currently working in the youth protection (YP) system. To this end, we analyzed data collected as part of a needs assessment designed to inform the development of a YP intervention program (123 questionnaires and 20 individual and group interviews). The results highlight a considerable gap between the initial and ongoing training received by practitioners and the skills needed to effectively and ethically involve children in decisions affecting them. However, practitioners do not seem to consider child participation as a priority topic to be included in a training program for YP practitioners. A number of contextual factors influence practitioners’ willingness to address children’s rights and participation issues in a training program.